Optimalisasi Kompetensi Kerja Melalui Program Praktek Kemahiran Hukum II bagi Mahasiswa Magang di Kanwil Kemenkum Kalteng - Rizky Hairiana; Almas Jaitun; Ahmad Sukma Nugraha; Nadilla Oktaviany; Nurul Nurul; Noor Adiyati; Rafik Patrajaya (Lembaga Pengembangan Kinerja Dosen, 2025)
The Legal Proficiency Practice Program II is an activity designed to connect the academic competence of students with the needs of work in legal institutions, one of which is the Regional Office of the Ministry of Law in Central Kalimantan. The main problem raised in this activity is how the optimization of student work competence can be achieved through direct involvement in the legal bureaucracy environment. The purpose is to provide a real professional experience, strengthen students' understanding of legal and administrative tasks, and form a professional identity as a prospective legal practitioner. The methods used include the placement of students with a rotation system in various work units for 30 days, observation of bureaucratic activities, involvement in substantive and administrative tasks. The implementation results show that the direct involvement of students in various work units can improve technical competencies, such as document management, meeting assistance, and information services, as well as develop non-technical competencies such as work ethics, communication, discipline, and time management. The internalization of PASTI values and the reflection process through the logbook also strengthens the formation of students' professional identity. Overall, the PKH II program is proven to be effective in optimizing the work competence of students and increasing their readiness to enter the world of the legal profession.